Scientific and technological mapping of Araceae Juss.: A projection for biological activities (Research, Society and Development, 2022)
Araceae Juss is a family with great chemical and biological potential due to its ethnopharmacological uses and chemical properties. This study, therefore, is a scientific and technological prospection in international databases of articles and patents on the biological activity of Araceae. India is the country with the highest number of scientific research with 28 records, with the highest number in Scopus (23), China and the United States are in second and third position, respectively, while Brazil is in fourth position. The areas with the highest number of indexed works were Pharmacy, Toxicology and Pharmaceuticals (23.6%) followed by Environmental Sciences (22.1%) and Agriculture and Biological Sciences (11.6%). Applications for patent filings began in 1949 (n=1), reaching a threshold in 2020 (n=153), based on the EPO. China is the country with the highest number of technological production involving the biological activities of the taxon, with 713 indexes, followed by the United States of America (n=378) and Japan (n=150), while Brazil presented only 13 published patents. In relation to CIP 252 patents comprise the subclass C12N15. It is concluded that the biological activities of the family are being a source for several researches, however, Brazil as a country with great family diversity, presents itself well below in the number of publications, which is due to the fact of little collaboration between companies and institutions and also by the delay in registering patents in the country.